Sodium–glucose cotransporter-2 inhibitor alleviated atrial remodeling in STZ-induced diabetic rats by targeting TLR4 pathway - Zhan, Xiaoping; Cheng, Lijun; Huo, Ning; Yu, Lin; Liu, Changle; Liu, Tong; Li, Guangping; Fu, Huaying (Frontiers in Cardiovascular Medicine, 2022)
Purpose: The mechanism of sodium–glucose-cotransporter-2 inhibitor (SGLT-2i) reducing the incidence of atrial fibrillation remains unclear. We hypothesis sodium–glucose-cotransporter-2 inhibitor alleviated atrial remodeling in STZ-induced diabetic rats by targeting TLR4 pathway. Methods: 42 Rats were randomly assigned into three groups: Control group (CON group), Diabete group (DM group): diabetes mellitus rats were established by 65 mg/kg streptozotocin (STZ) intraperitoneal injection, Diabete+Dapagliflozin group (DM+DAPA group): diabetic rats were given DAPA gavage administration (DAPA 2mg/kg/d for four weeks by gavage administration), 14 rats in each group. Epicardial multiple lead recording and intracardiac electrophysiology study were performed to investigated the electrical remodeling in the heart and the atrial fibrillation inducibility in each group. Western blot analysis and Real-time PCR were used to determine the protein and mRNA expression of toll-like receptor-4(TLR4), interleukin receptor associated kinase 1(IRAK1), tumor necrosis factor receptor associated factor 6 (TRAF6), nuclear factor-kappa B (NF-κB) and type I collagen (Collagen I). Results: Compared with rats in CON group, rats in DM group showed marked myocardial fibrosis, ectopic pacing excitement, reduced conduction velocity, decreased cardiac function, TLR4/IRAK1/TRAF6/NF-κB and collagen I proteins expression were increased and higher incidence of atrial fibrillation (27.3%). Parts of these changes were reversed by treatment of DAPA. Incidence of atrial fibrillation was decreased in DM+DAPA group (2.8%). Conclusions: SGLT-2i Dapagliflozin prevented diabetic rats atrial remodeling and reduced the inducibility of atrial fibrillation by targeting TLR4/IRAK1/TRAF6/NF-κB inflammatory pathway.